Validitas dan Reliabilitas Tes Diagnostik Two-tier untuk Mengidentifikasi Konsep Alternatif pada Topik Gaya Antarmolekul - Asriah N. Mardiyyaningsih; Erlina Erlina; Maria Ulfah; Azwa Fadilla Wafiq (Jurnal Penelitian Pendidikan IPA, 2023)
Alternative conceptions or misconceptions is believed as the main barrier for most students who learn chemistry. Students who hold alternative conceptions will struggle to understand the advanced concepts. Therefore, identifying those alternative conceptions is important. In this study a diagnostic test was designed and developed to identify students’ alternative conceptions about intermolecular forces (IMFs). The diagnostic test developed in this study consist of 19 multiple choice questions with open reason. The test was administered to 88 university students who learn chemistry. Data collected were analyzed using SPSS. The validity and the reliability of the test were 0.526 and 0.878 respectively. The result indicates that the test is valid and reliable. The mean difficulty value and discriminatory index are 0.623 and 0.45 respectively. The findings of the item analysis showed that the test is in moderate difficulty and the discriminatory of the test is in good category. Meanwhile, the average distractor effectivity for the diagnostic test is 3 options (out of 4 options), which means the distractors are in good category and well function. Those findings indicate that the two-tier diagnostics test could be used to identify students’ alternative conceptions and understanding about IMFs.